Pharmacodynamic Evaluation of a Single Dose versus a 24-Hour Course of Multiple Doses of Cefazolin for Surgical Prophylaxis - Aaron Heffernan; Jowana Alawie; Steven C Wallis; Saiyuri Naicker; Santosh Adiraju; Jason A. Roberts; Fekade Bruck Sime (MDPI AG, 2021)
The optimal perioperative duration for the administration of cefazolin and other prophylactic antibiotics remains unclear. This study aimed to describe the pharmacodynamics of cefazolin for a single 2 g dose versus a 24 h course of a 2 g single dose plus a 1 g eight-hourly regimen against methicillin-susceptible Staphylococcus aureus. Static concentration time-kill assay and a dynamic in vitro hollow-fibre infection model simulating humanised plasma and interstitial fluid exposures of cefazolin were used to characterise the pharmacodynamics of prophylactic cefazolin regimens against methicillin-sensitive Staphylococcus aureus clinical isolates. The initial inoculum was 1 × 105 CFU/mL to mimic a high skin flora inoculum. The static time-kill study showed that increasing the cefazolin concentration above 1 mg/L (the MIC) did not increase the rate or the extent of bacterial killing. In the dynamic hollow-fibre model, both dosing regimens achieved similar bacterial killing (~3-log CFU/mL within 24 h). A single 2 g dose may be adequate when low bacterial burdens (~104 CFU/mL) are anticipated in an immunocompetent patient with normal pharmacokinetics.